Biomechanical evaluation of arthroscopic all-inside meniscus repairs - Gunes, Taner; Bostan, Bora; Erdem, Mehmet; Asci, Murat; Sen, Cengiz; Kelestemur, Mehmet Halidun (Springer, 2009)
Viper is a new device for arthroscopically all-inside meniscal repairing. In previous studies about Viper device, procedures were not applied arthroscopically despite this device has been designed for arthroscopic application. In this study, we evaluated primary fixation strength of arthroscopically applied meniscal repair using Viper device to obtain better clinical relevance. Two centimeter in length meniscal tear 2-3 mm far from periferic edge of medial meniscus of 50 calves were created arthroscopically. The menisci were divided into five groups including 10 menisci in each. In group 1, tears were repaired by outside-in vertical loop suture technique with No: 0 PDS. Tears were fixed by all-inside vertical suture by using Viper device with No: 0 PDS in group 2. In meniscal implant groups, RapidLoc, H-Fix, and Clearfix were applied in groups 3,4, and 5, respectively. Primary fixation strength of repairing techniques were evaluated with bio-mechanical testing machine. Fixation strengths determined in groups 1 and 2 were detected as 145 +/- A 13 and 136 +/- A 33 N, respectively. There was no difference in pull-out strength between groups 1 and 2. Fixation strengths in these two groups were significantly higher compared to groups 3, 4, and 5. There was no significant difference between group 3 (33 +/- A 6 N) and 5 (28 +/- A 6 N) in terms of fixation strengths whereas fixation strengths of these two groups were significantly higher compared to group 4 (20 +/- A 3 N) (P = 0.005, P = 0.018, respectively). All-inside vertical suture technique using Viper device revealed comparable primary fixation strength with outside-in vertical suture technique for meniscal repair. We suggest that the Viper device is safe and reliable for meniscal repair.
Keywords: Meniscus; Repair; Arthroscopy; Viper device